ANALISIS PENERAPAN SAFETY WORKING PERMIT SEBAGAI UPAYA PELAKSANAAN K3 PADA PT. X TAHUN 2023 - Junianto Patra (2023)
Safety Working Permit is a risk control system from work activities to ensure work procedures implementations are safe and according occupation category. Companies with high-risk occupation are required to use work permit system in accordance with Government Regulation No. 50 of 2012 concerning the Occupational Health and Safety Management System. PT. X is a company with high-risk work activities related to electricity. Safety Working Permit application at PT. X has been implemented since 2019, but the implementation remains suboptimal and marked by lack of worker knowledge about Safety Working Permit. This study aims to analyze the application of Safety Working Permit as an effort to implement K3 at PT X 2023. This study used qualitative methods with case study design. Research using in-depth interviews and observations with checklist forms adapted to guidelines of International Association Oil and Gas Producers. The results showed that PT X's Safety Working Permit system still not meet the guidelines used by researchers. The incomplete of work permit is the reason for non-optimal implementation of Safety Working Permit system. It is suggested that companies needs to determine guidelines in the implementation of work permits so that the implementation of work permits run optimally.